The answer is the first option, <-20, -42>.
We can find this by first finding what -2u would equal by multiplying <5, 6> by -2. This gives us <-10, -12>.
Then we need to find out what 5v is equal to, by multiplying <-2, -6> by 5 to get <-10, -30>.
Now that we know what -2u and 5v are, we can substitute them into the equation and get
<-10, -12> + <-10, -30>, which we can split up into -10 - 10 = -20, and -12 - 30 = -42, so your final answer is <-20, -42>.
I hope this helps!
3 is the answer because the a correct
Answer:
![y = -3x + 6\\](https://tex.z-dn.net/?f=y%20%3D%20-3x%20%2B%206%5C%5C)
Step-by-step explanation:
Find the gradient of the equation
![\frac{Difference in y}{Difference in x} \\\\\frac{6 - - 6}{0 - 4} = \frac{12}{-4} = -3](https://tex.z-dn.net/?f=%5Cfrac%7BDifference%20in%20y%7D%7BDifference%20in%20x%7D%20%5C%5C%5C%5C%5Cfrac%7B6%20-%20-%206%7D%7B0%20-%204%7D%20%20%3D%20%5Cfrac%7B12%7D%7B-4%7D%20%3D%20-3)
The equation will have the gradient -3x
Use the general equation of a line, and substitute the coordinates in to find the y-intercept.
![y = x + c\\ y = -3x + c\\](https://tex.z-dn.net/?f=y%20%3D%20x%20%2B%20c%5C%5C%20y%20%3D%20-3x%20%2B%20c%5C%5C)
(4, -6)
![-6 = -3(4) + c\\ -6 = -12 + c\\ -6 + 12 = c\\ c = 6](https://tex.z-dn.net/?f=-6%20%3D%20-3%284%29%20%2B%20c%5C%5C%20-6%20%3D%20-12%20%2B%20c%5C%5C%20-6%20%2B%2012%20%3D%20c%5C%5C%20c%20%3D%206)
![6 = -3(0) + c\\ 6 = 0 + c\\ c = 6](https://tex.z-dn.net/?f=6%20%3D%20-3%280%29%20%2B%20c%5C%5C%206%20%3D%200%20%2B%20c%5C%5C%20c%20%3D%206)
(0, 6)
![6 = -3(0) + c\\ 6 = -0 + c\\ c = 6](https://tex.z-dn.net/?f=6%20%3D%20-3%280%29%20%2B%20c%5C%5C%206%20%3D%20-0%20%2B%20c%5C%5C%20c%20%3D%206)
The equation of the line is
![y = -3x + 6\\](https://tex.z-dn.net/?f=y%20%3D%20-3x%20%2B%206%5C%5C)
Answer:
Step-by-step explanation:
Answer:
5) √(3² + 5²) = √34
6) √(4² - 3²) = √7
7) the visible answers all say exactly the same thing in different ways and are all correct.
Step-by-step explanation: